BURHAN AL-DIN AL-NASAFI’S EDUCATIONAL PHILOSOPHY AND ITS ROLE IN MODERN EDUCATION - G‘uzarov O‘tkir Umbarovich (The Conference Hub, 2025)
Burhan al-Din al-Nasafi was a prominent Islamic scholar and jurist whose contributions to education remain significant. His philosophical approach to knowledge emphasized rational thinking, religious principles, and ethical conduct. Nasafi’s works, particularly in Islamic jurisprudence and theology, shaped the intellectual landscape of his time and continue to influence contemporary Islamic studies.This paper explores Nasafi’s educational philosophy, focusing on his methodology, key principles, and their relevance to modern education. It examines how his balanced approach—integrating religious sciences with rational thought—can contribute to contemporary educational models, particularly in fostering critical thinking, ethical awareness, and interdisciplinary learning. By analyzing his legacy, this study highlights the enduring value of classical Islamic education in addressing current educational challenges.
Keywords: Burhan al-Din al-Nasafi, educational philosophy, Islamic education, rational thinking, jurisprudence, theology, modern education, ethical conduct, interdisciplinary learning, critical thinking.